Evaluating the Impact of a Clinical Decision Support Tool to Reduce Chronic Opioid Dose and Decrease Risk Classification in a Veteran Population. Issue 4 (April 2018) - Patel, Shardool; Carmichael, Jan M.; Taylor, Janice M.; Bounthavong, Mark; Higgins, Diana T.
Background: Chronic opioid therapy–clinical reminder (COT-CR) is a decision support tool to prompt providers to carefully assess patients prescribed chronic opioids. This tool was developed to address inappropriate opioid prescribing.Objective: To determine COT-CR's impact on reducing morphine equivalent monthly dose (MEMD) and risk index for overdose or serious prescription opioid-induced respiratory depression (RIOSORD) values in veterans receiving chronic opioids.Methods: This retrospective cohort review matched patients with a complete COT-CR to patients with an incomplete COT-CR using propensity scores. In the primary aim, an interrupted time series design evaluated for changes in MEMD 12 months before and 6 months after the index date. The index date was the first pain or primary care provider visit post COT-CR installation. In the secondary aims, a retrospective cohort design was used to evaluate the changes in RIOSORD index score and risk class 6 months after the index date.Results: After matching, 3801 patients were included in the complete and incomplete COT-CR groups, respectively. Greater average reduction in MEMD (−11.6 MEMD; 95% CI = −0.97 to −22.25 MEMD; P = 0.032) and RIOSORD index score (−0.53 RIOSORD index score; 95% CI = −1.00, −0.05 RIOSORD index score; P = 0.030) was observed in patients with a complete COT-CR compared to patients with an incomplete COT-CR. Differences in RIOSORD risk class were insignificant.Conclusion: Completing the COT-CR was associated with reduced MEMD and RIOSORD values. This suggests that active monitoring can change prescribing patterns, thereby, reducing the overall risk of opioid overdose in at-risk veterans.